Review Article: IDENTIFIKASI SENYAWA KIMIA DAN UJI AKTIVITAS ANTIHIPERTENSI TUMBUHAN JAMBLANG - Azzahra, Ayu Jasmine; Amelia, Azzahra; Budiyanti, Lia Eka; Hidayah, Himyatul (Peneliti.net, 2024)
The jamblang plant is a type of fruiting tree from the Myrtaceae family that has many health benefits, one of which is to treat hypertension. This study aims to identify chemical compounds and test the antihypertensive activity of jamblang plant (Syzygium Cumini L.). This systematic review was carried out by identifying articles in several databases (Google Scholar, PubMed, ScienceDirect, and ResearchGate). The article selection process uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to create a flow diagram with research inclusion and exclusion criteria. Results showed that ethanol extract of jamblang plant contains flavonoids, tannins, saponins, steroids, terpenoids, anthroquinones, alkaloids, catechins, glycosides, and phenols. Antihypertensive activity test showed that ethanol extract of jamblang plant has ACE inhibition activity with IC50 value of 128.4 mg/mL. Conclusion The jamblang plant has potential as a source of natural antihypertensive compounds that can be used as an alternative treatment for hypertension.